Suppressing effect of a saikosaponin-enriched extract of Bupleurum falcatum on alcohol and chocolate self-administration in rats - Maccioni, Paola; Colombo, Giancarlo; Lorrai, Irene; Lee, Jung Hwan; Pel, Pisey; Chin, Young-Won; Kwon, Hak Cheol (Taylor & Francis, 2022)
Recent studies demonstrated that saikosaponin (SS) A and other SSs extracted from Bupleurum falcatum L. (Apiaceae) roots abolished different behaviours motivated by drugs of abuse and palatable foods in rats. The present study was designed to investigate the effect of an SS-enriched extract fraction of B. falcatum roots on operant, oral self-administration of alcohol and chocolate in rats. To this end, female Sardinian alcohol-preferring and Wistar rats were trained to lever-respond for alcohol (15% v/v) and chocolate (5% w/v powdered Nesquik in water), respectively. Acute treatment with B. falcatum extract (0, 0.75, 1.5, and 3 mg/kg, i.p.) reduced, in a dose-related manner, both alcohol and chocolate self-administration. These data confirm the notion that B. falcatum extracts may be a valuable source of pharmacological agents with anti-addictive and anorectic potential. The use of experimental procedures with predictive validity for the human disease adds strength to the translational potential of these results.